The Impact of Antitumor Treatment on Cancer Patients with COVID-19: A Systematic Review and Meta-Analysis - Ananto, Farizky Jati; Purwanto, Heru; Ayuda, Caesar; Wibiseno, Dono Marsetio; Putra, Probo Yudha Pratama; Wardhana, Burhan Mahendra Kusuma; Putra, Doddy Setya Adi (Indonesian Journal of Cancer, 2024)
Background: Cancer is a chronic disease that can cause various complications, decrease the immune system, reduce quality of life, and even lead to death. In addition, the COVID-19 pandemic in various countries has had a significant adverse impact on patients. This study analyzed the impact of various antitumor treatments on cancer patients with COVID-19. Methods: This meta-analysis was conducted according to the PRISMA – P pathway. Source searches were conducted in PubMed, Cochrane Library, Research Gate, and Science Direct in cancer patients with COVID-19 receiving various types of antitumor treatment. Analysis was performed using RevMan V.5.3 software with the outcome of mortality rate and severe COVID-19. Results: Twenty-five observational studies met the inclusion criteria with a total of 21,940 patients. There was no significant difference in mortality rate (OR 1.08, 95% CI 0.99 – 1.18, p = 0.09), but there was a significant difference in severe COVID-19 (OR 1.19, 95% CI 1.02 – 1.39, p = 0.02). Immunotherapy provided the most significant worsening of both mortality rate (OR 1.39, 95% CI 1.17 – 1.64, p = 0.0001) and severe COVID-19 (OR 1.82, 95% CI 1.23 – 2.71, p = 0.003). There were no significant differences in other antitumor treatments. Conclusions: Antitumor treatment does not have a significant impact on mortality rate, but has a significant impact on worsening the degree of COVID-19. Among all the antitumor therapies that provide the highest potential for worsening is immunotherapy.